1993
DOI: 10.1128/iai.61.12.5279-5285.1993
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the roles of antilipopolysaccharide and anti-cholera toxin immunoglobulin A (IgA) antibodies in protection against Vibrio cholerae and cholera toxin by use of monoclonal IgA antibodies in vivo

Abstract: Secretory immunoglobulin A (IgA) antibodies (sIgA) directed against cholera toxin (CT) and surface components of Vibrio cholerae are associated with protection against cholera, but the relative importance of specific sIgAs in protection is unknown. A monoclonal IgA directed against the V. cholerae lipopolysaccharide (LPS), secreted into the intestines of neonatal mice bearing hybridoma tumors, was previously shown to provide protection against a lethal oral dose of 107 V. cholerae cells. We show here that a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(42 citation statements)
references
References 36 publications
1
41
0
Order By: Relevance
“…In previous studies we observed that the rate of tumour growth in vivo tends to roughly parallel the rate of growth of the corresponding hybridoma cells in culture [4,5]. In this study, mice injected with IgA hybridoma cells began to show visible tumours at the injection site 2 days before those with IgG hybridoma cells.…”
Section: Histological Organization Of Backpack Hybridoma Tumourssupporting
confidence: 62%
See 2 more Smart Citations
“…In previous studies we observed that the rate of tumour growth in vivo tends to roughly parallel the rate of growth of the corresponding hybridoma cells in culture [4,5]. In this study, mice injected with IgA hybridoma cells began to show visible tumours at the injection site 2 days before those with IgG hybridoma cells.…”
Section: Histological Organization Of Backpack Hybridoma Tumourssupporting
confidence: 62%
“…It has been difficult to directly assess the contribution of secretory IgA to mucosal protection, however, because of the technical difficulties in collecting local mucosal secretions and the complexity of immune responses after oral immunization or microbial challenge. One approach to this problem has been to generate monoclonal, dimeric IgA antibodies that can be fed orally [4,5], delivered to the respiratory mucosa by nose drops [6], or applied directly to epithelial cells in culture [7,8]. Such studies have demonstrated that specific IgA antibodies can indeed protect against viral infection, bacterial invasion and toxin binding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of protection in the mouse model is not known and may depend on the specificity of the antibody. The use of Fab fragments which do not fix complement and the efficacy of anti-LPS IgA which does not fix complement, suggests that complement is not required for protection in the infant mouse model (8,217). The prevention of colonization is a major finding in studies that examine the protective capacity of various antisera or antibodies.…”
Section: The Mouse Model and Protective Isotype And Mechanismmentioning
confidence: 99%
“…Mucosal antibodies may protect against invasive infections but still permit colonization, which is the case for commensal bacteria in the gut [31,32]. On the other hand, they may eradicate microbes from the mucosal surface, as demonstrated for Respiratory Syncytial Virus (RSV) and Haemophilus influenzae in the respiratory tract [33,34], or Vibrio cholera, Helicobacter felis and Salmonella typhimurium in the gut [35][36][37]. Although persistent colonization or eradication may be determined by the quantity of the local antibodies [38,39], there is also evidence that their specificity to the different microbial epitopes [40], as well as their avidity [41], is important.…”
Section: Discussionmentioning
confidence: 99%